Percutaneous drain for high risk cases of perforative peritonitis - L., Thirumanikandan P.; T., Arasu V. (International Surgery Journal, 2016)
Background: Perforative peritonitis is most common general surgery emergency encountered. It is also associated with high operative mortality and morbidity. Most cases present late on second and third day with severe peritonitis and hemodynamic instability. Resulting in hypotension and circulatory shock due to septicaemia and third space fluid loss. In these patients conventional immediate laparotomy and perforation closure was associated with high mortality. Henceforth we managed those high risk patients with percutaneous drain and conservative Taylor’s regimen was followed. Methods: Aim of this study was to analyse series of high risk perforation cases managed with percutaneous drain under local anesthesia for whom conventional surgery of immediate laparotomy were associated with high mortality rates. Those conservatively managed patients were serially monitored and put on Taylor’s regimen previously used for sealed early perforation. Results: Retrospectively 9 cases of high risk perforative peritonitis managed with percutaneous drain were studied and we found that mortality rate was 22% compared to more than 60% in cases taken up for immediate laparotomy. Conclusions: High risk patients for whom conventional surgery is associated with increased mortality, percutaneous drain under local anaesthesia and improving the hemodynamic status by non-operative Taylor’s regimen seems to be associated with decreased mortality and morbidity.